Comparative study of quality of subarachnoid blocks for caeasarean section by using bupivacaine alone & bupivacaine - fentanyl combination - Paul, Manisha; Dhar, Satyajit; Banik, Debasish; Huda, AK Quamrul; Hossain, Moinul; Choudhury, Gulshan Ara; Alam, AKM Shamsul; Chowdhury, AYF Elahi (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: The popularity of subarachnoid block (SAB) in cesarean section in recent times is due to better understanding of the physiological changes associated with it and proper appreciation of its advantages & complications. Hyperbaric bupivacaine in adequate dose (12mg or more) for SAB often causes complications like hypotension, shivering, nausea, vomiting, chest pain & epigastric pain. Objectives: The aim of study is to reduce these complications by using bupivacaine-fentanyl combination. Method: 150 patients of ASA grade I & II waiting for cesarean section under SAB were randomly allocated into three equal groups. Group A : Received 0.5% hyperbaric bupivacaine-10 mg (2ml) Group B : Received 0.5% hyperbaric bupivacaine-10 mg (2ml) & fentanyl- 15 ?g [0.3ml] Group C : Received 0.5% hyperbaric bupivacaine - 8 mg (1.6ml) & fentanyl- 15 ?g. [0.3ml] Parametric data like pulse, blood pressure, among the groups were analyzed by ANOVA test & nonparametric data like chest discomfort, epigastric pain, nausea, vomiting were analyzed by chi-square test. Results: In this study we found better analgesia & quality of block in bupivacaine-fentanyl group than bupivacaine alone group (p<.001). Conclusion: By adding fentanyl we can reduce the dose of bupivacaine & also improve the quality of block. DOI: http://dx.doi.org/10.3329/jbsa.v22i2.18144 Journal of BSA, 2009; 22(2): 61-65